Improving the follow-up of microbiology results: the origins of the Pink Book. Issue 1 (29th October 2014) - Boyle, Henry; Hunt, Charlie; McIlroy, Catherine; Qureshi, Imran
Abstract: Failure to check microbiology results put patients at risk of prolonged infections, resulting in increased morbidity and mortality from sepsis. There are some electronic systems designed to address this risk although they are rarely used in the hospital setting. In many hospitals the follow-up of microbiology results for discharged patients is reliant upon individual doctor's vigilance or ad hoc lists. Our intervention, the 'Pink Book', provides a simple, cost effective system to follow-up microbiology results for discharged patients. This simple paper based system enables prompt, effective, efficient follow-up of microbiology results, saving our paediatric department an estimated 1.5 hours per week, £17, 440 per year and helping to prevent one case of inadequately treated infection per month. This project highlights how small scale, simple interventions at the local level, born out of the frustration at existing inefficient systems, can make great improvements to patient safety and the efficiency of healthcare.